Biosurfactant Production Using Mutant Strains of Pseudomonas aeruginosa and Bacillus subtilis from Agro-industrial Wastes - Samson A. Adejumo; Angus Nnamdi Oli; Ebere Innocent Okoye; Calistus Dozie Nwakile; Chioma Miracle Ojiako; Ugochukwu Moses Okezie; Ifeanyi Justin Okeke; Chijioke M. Ofomata; Anthony A. Attama; Jude N. Okoyeh; Charles Okechukwu Esimone (Tabriz University of Medical Sciences, 2021)
Purpose: Biosurfactants are applied in drug formulations to improve drug solubility and in some cases, treat diseases. This study is focused on generating, extracting, purifying and then characterizing biosurfactants from bacterial isolates of palm oil wastes and abattoir soil origins. Methods: Eight bacteria were isolated from the soil and sludge samples, out of which four (50%) were found to produce biosurfactants. Bacillus subtilis (37.5%) and Pseudomonas aeruginosa (50%) were isolated and identified from these samples using mineral salt medium, nutrient agar and Cetrimide agar. Mutant isolates of B. subtilis BS3 and P. aeruginosa PS2 were used to produce biosurfactants using mineral salt medium as enrichment medium and extraction was done using membrane filter. Results: The mutant strains B. subtilis BS3 and P. aeruginosa PS2 generated biosurfactants that displayed significant solubility and dissolution properties by enhancing the percentage solubility of piroxicam to 62.86 and 54.29% respectively, and achieved 51.71 and 48.71% dissolution of the drug in 0.1N HCl. Conclusion: From the results obtained, the produced biosurfactants could serve as a better alternative to conventional surfactants. Notably, the study indicated that the biosurfactant produced by mutant strain of B. subtilis produced more potent activities (surface tension reduction ability, high emulsification) than those of P. aeruginosa.